Update on the Nutrition Innovation Lab Approach. - Griffiths, Jeffrey.; Webb, Patrick, 1959-; Ghosh, Shibani. (Tufts University. Tisch Library., 2017)
This presentation was given to USAID Malawi and covers what kind of work the Nutrition Innovation Lab does.; Keywords: Nutrition Innovation Lab, operations research, capacity building, policy analysis, Malai Tufts University.; NIL Presentations 2013-2015.